2011
DOI: 10.1172/jci44999
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of TLR6 in a mouse model of asthma is mediated by IL-23 and IL-17A

Abstract: TLRs are a family of receptors that mediate immune system pathogen recognition. In the respiratory system, TLR activation has both beneficial and deleterious effects in asthma. For example, clinical data indicate that TLR6 activation exerts protective effects in asthma. Here, we explored the mechanism or mechanisms through which TLR6 mediates this effect using mouse models of Aspergillus fumigatus-induced and house dust mite antigen-induced (HDM antigen-induced) chronic asthma. Tlr6 -/-mice with fungal-or HDM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 57 publications
2
59
0
1
Order By: Relevance
“…Although IL-17 has been shown to play a role in neutrophilic asthma, 44 it has also been shown to be a negative regulator of established allergic asthma. 45,46 The baseline elevation of IL-17 in RAGE KO mice may thus impede the initiation of a primary asthmatic response. Moreover, it may account for the subtle differences in airway responsiveness to methacholine challenge between naive saline-treated WT and RAGE KO mice (RAGE KO mice treated with saline showed an elevated Rn parameter compared with WT mice thus treated), as a number of studies have indicated a role for IL-17 in promoting airway hyperresponsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Although IL-17 has been shown to play a role in neutrophilic asthma, 44 it has also been shown to be a negative regulator of established allergic asthma. 45,46 The baseline elevation of IL-17 in RAGE KO mice may thus impede the initiation of a primary asthmatic response. Moreover, it may account for the subtle differences in airway responsiveness to methacholine challenge between naive saline-treated WT and RAGE KO mice (RAGE KO mice treated with saline showed an elevated Rn parameter compared with WT mice thus treated), as a number of studies have indicated a role for IL-17 in promoting airway hyperresponsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…RORγt is reported to specifically determine Th17 lineage development and is mutually exclusive in Foxp3 expression in CD4 + T cells, as Foxp3 inhibits RORγt expression and Th17 development (26). IL-23 expression has been reported to play a role in promoting Th17 expansion by directly affecting T cells and initiating the release of TGF-ß and IL-6 by DCs (8). Notably, in Foxp3 mRNA-treated mice, RORγt, IL-23, and IL-17A expression levels were significantly downregulated, concomitant with the significant improvement observed in AHR, cellular infiltration, and rebalancing of Th2 responses ( Figure 3, 4, and 6).…”
Section: Foxp3-induced Asthma Protection Is Mediated Through An Il-10mentioning
confidence: 99%
“…IL-17 levels are increased in the circulation and airway fluids of asthmatic patients, where they correlate with disease severity (5). Experimental studies report that IL-17 and its upstream mediator, IL-23, can exacerbate or lessen Th2-mediated inflammation in a time-and source-dependent manner (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Alike IL-17A, the role of IL-23 in asthma pathogenesis is discussed controversially. IL-23 expression is elevated in mice with experimental asthma and exogenous administration or local overexpression of IL-23 resulted in aggravation of the disease (42,43). In contrast, lack of IL-23 had no effect on the development of experimental asthma in mice (34).…”
Section: Discussionmentioning
confidence: 97%